2016
DOI: 10.1038/srep30247
|View full text |Cite
|
Sign up to set email alerts
|

Systemic localization of seven major types of carbohydrates on cell membranes by dSTORM imaging

Abstract: Carbohydrates on the cell surface control intercellular interactions and play a vital role in various physiological processes. However, their systemic distribution patterns are poorly understood. Through the direct stochastic optical reconstruction microscopy (dSTORM) strategy, we systematically revealed that several types of representative carbohydrates are found in clustered states. Interestingly, the results from dual-color dSTORM imaging indicate that these carbohydrate clusters are prone to connect with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The spatial distribution pattern of glycans has also been demonstrated to affect the stability and behavior of cell membranes ( 86 , 87 ). The LEL specific GCs have recently been reported to exist as clusters in a confined region ( 88 ). The region-specific micro-heterogeneity in the abundance of T disaccharide i.e., galactosyl (β-1,3) N-acetylgalactosamine, galactose of the T antigen, and N-acetyl glucosamine (cognate glycans for ABL, JAC and LEL, respectively) observed in the lectin cytochemistry experiments reflect distinctive and spatially distributed, putatively functional micro-domains on the buffalo sperm.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial distribution pattern of glycans has also been demonstrated to affect the stability and behavior of cell membranes ( 86 , 87 ). The LEL specific GCs have recently been reported to exist as clusters in a confined region ( 88 ). The region-specific micro-heterogeneity in the abundance of T disaccharide i.e., galactosyl (β-1,3) N-acetylgalactosamine, galactose of the T antigen, and N-acetyl glucosamine (cognate glycans for ABL, JAC and LEL, respectively) observed in the lectin cytochemistry experiments reflect distinctive and spatially distributed, putatively functional micro-domains on the buffalo sperm.…”
Section: Discussionmentioning
confidence: 99%
“…There are many kinds of carbohydrates in plants [40][41][42]. Different kinds of carbohydrates can participate in maintaining stability of cell membrane structure function [43]. However, there are also significant differences in the types of carbohydrates accumulated by different varieties of plants under cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the core structures of N‐linked and O‐linked oligosaccharides,13 the common monosaccharide residues are the following ones:13 N‐acetyl‐D‐glucosamine (GlcNAc), N‐acetylgalactosamine (GalNAc), fucose (Fuc), mannose (Man), galactose (Gal), and sialic acid (Sia). Moreover, based on our related studies on carbohydrates6,14, 15, 16 we found the carbohydrates tended to form clusters as functional domains, where various functional glycocongujates locate via being cross‐linked by carbohydrate‐binding proteins (CBPs), with the contributions of lipid rafts as the stable factors and actin cytoskeletion as restricted factors. These findings indicate that the organization of carbohydrates not only represents the distributions of membrane glycoconjugates, but also is related to the membrane functional domains and membrane cytoskeletion.…”
Section: Introductionmentioning
confidence: 93%